Metódo multicriterio para apoyo a la planificación hídrica - Martín-ortega, J.; Berbel Vecino, J. (Observatorio Medioambiental, 2007)
Economic analysis on the Water Framework Directive is, among other aspects, in the phase of characterization for present and future uses of the water and also the preparation of the Program of Measures based on the cost-effectiveness analysis. This article presents the results of water use economic characterization for the Guadalquivir River Basin (Southern Spain), which shows an expected unsustainable situation with consumption of over 50% of renewable resources. Due to the ecological and social complexity of environmental conflicts, authors advocate for a multicriteria approach beyond the cost-benefit analysis, as an input of water resource planning. Afirst exercise on hierarchical social preferences evaluation, showing the relevance of the environmental criteria, is presented on this paper.